Жоғары оқу орнында студенттерді патриоттыққа тəрбиелеудің əдіснамалық мəселелері - Айдналиева, Н.А. (My University, 2016)
The article deals with role of patriotic upbringing at the formation of the culture of international association future teacher at the institute. Author pays attention to the connection of the ethnopedagogical culture and the culture of international association.
Keywords: patriotic upbringing; interethnic dialogue; upbringing at the institute; the educational events; ethnopedagogical culture